Program Monitoring dan Otomasi Tangki Timbun dengan Sistem SCADA (Supervisory Control And Data Acquisition) di Kilang PPSDM Migas - Desy Kurnia Puspaningrum (Swara Patra, 2019)
Storage tank is one component of the processing unit at the PPSDM Migas refinery. The Variation in number and size of tanks makes the operators difficult to calculate the tanks capacity, which until now has been done manually which is prone to errors. Besides, the operator cannot present the realtime data. To minimize this problem, an automation and monitoring system design of tank capacity in PPSDM Migas Refinery was made by using the SCADA System. SCADA is a control system that is equipped with HMI (Human Machine Interface) facilities that can display field data that is more user friendly and easier for ordinary people to understand. This design uses Allan Bradley type Micro Logix PLC (Programmable Logic Controller) with RS Logix 500 software, and HMI Wonderware.